2004
DOI: 10.1002/jcb.20246
|View full text |Cite
|
Sign up to set email alerts
|

Tumor–host interactions

Abstract: A number of malignant tumors interact with the host to cause a syndrome of cachexia, characterized by extensive loss of adipose tissue and skeletal muscle mass, but with preservation of proteins in visceral tissues. Although anorexia is frequently present, the body composition changes in cancer cachexia cannot be explained by nutritional deprivation alone. Loss of skeletal muscle mass is a result of depression in protein synthesis and an increase in protein degradation. The main degradative pathway that has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
5

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 29 publications
1
47
0
5
Order By: Relevance
“…Recently, it has been reported that ZAG activity in rodents is mediated via the b 3 -adrenoreceptor, with upregulation of the cAMP pathway (Russell et al 2004, Tisdale 2004, McDermott et al 2006. In a previous study, we reported that ZAG was primarily related to sperm forward motility in human semen (Ding et al 2007).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Recently, it has been reported that ZAG activity in rodents is mediated via the b 3 -adrenoreceptor, with upregulation of the cAMP pathway (Russell et al 2004, Tisdale 2004, McDermott et al 2006. In a previous study, we reported that ZAG was primarily related to sperm forward motility in human semen (Ding et al 2007).…”
Section: Introductionmentioning
confidence: 75%
“…The cAMP signaling pathway is reported to be involved in the process of lipolysis in adipocytes in many mammals, for which the b-adrenergic receptor is directly induced by ZAG (Russell et al 2002, 2004, Sanders & Tisdale 2004, Tisdale 2004, McDermott et al 2006. The crystalline structure of ZAG resembles a class I major histocompatibility complex (MHC) heavy chain, but, unlike other MHC-related proteins, ZAG does not bind the class I light-chain b 2 -microglobulin (Sanchez et al 1997(Sanchez et al , 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this aspect, recent determination of the crystal structure of FASN and molecular description of its active sites (Maier et al, 2008) would help in the development of improved inhibitors. Cancer cells also induce lipolysis in adipose tissue, a characteristic feature of cachexia, by producing lipid mobilisation factors (Tisdale, 2004). However, it is still not clear how the exogenous lipid mobilised from adipose tissue could affect the dependence of tumours on de novo fatty-acid synthesis.…”
Section: Fasn and De Novo Fatty-acid Synthesis As Promising Targets Omentioning
confidence: 99%
“…Depletion of lean body mass is the main characteristic of cachexia [2], but recent evidence has indicated that besides skeletal muscle depletion, cardiac proteins also play a role in affecting cardiac function [3,4].…”
Section: Introductionmentioning
confidence: 99%